Genre-Based Approach To Enhance University Students’ Ability And Creativity In Writing Narrative Story - Senny Suzanna Alwasilah (Departement of Mathematics Education, 2024)
Writing is widely recognized as a crucial skill for students in higher education to master. Given that writing is widely regarded as one of the most challenging skills, educators must adopt effective approaches in teaching this skill. the Genre-Based Approach (GBA) emerges as a potentially effective method to improve students' writing abilities and potentially address writing challenges. This present study aims to identify students’ ability in writing towards the use of a genre-based approach in teaching writing. Based on the findings and discussions, it was concluded that implementing the genre-based approach to enhance university students' writing’s ability in comprehending narrative texts revealed several key insights.